P73 and FoxJ1: Programming Multiciliated Epithelia. Issue 4 (April 2016) - Jackson, Peter K.; Attardi, Laura D.
Abstract : The mysteriously diverse phenotypes in mice lacking the p53 homolog p73 are recently unified by new analysis showing p73 is required for formation of multiciliated epithelia. p73 directly activates FoxJ1, the central transcriptional driver for multiciliation, and induces a host of genes critical for ciliogenesis.